1992
DOI: 10.1002/malq.19920380122
|View full text |Cite
|
Sign up to set email alerts
|

Representation of Posets

Abstract: In this paper we give new criterions for left distributive posets to have neatest representations. We also illustrate a construction that would embed left distributive posets into representable semilattices. MSC: 06A10, 06A12.Any poset (P, 5) has at least two representations [l] as a poset (Q, S). One of these two representations has the property that the image of the supremum of any (finite or infinite) subset A of P is the union of the images of the elements of A, while the other representation has the prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…A step in this argument assumes the existence of finite meets, which is invalid in the more general setting of posets. This is a symptom of a deeper problem, as a simple generalization of the axiom schema for semilattices (such as appears as the condition LMD in [5], see definition 1.4 below) is not expressive enough for the poset situation (see example 1.5, where it is shown that LMD is not a necessary condition for a poset to have a representation). Note that the question of whether LMD is a sufficient condition for representability with respect to all meets and binary joins is raised as open in [5], and appears not to have been resolved.…”
Section: Introductionmentioning
confidence: 99%
“…A step in this argument assumes the existence of finite meets, which is invalid in the more general setting of posets. This is a symptom of a deeper problem, as a simple generalization of the axiom schema for semilattices (such as appears as the condition LMD in [5], see definition 1.4 below) is not expressive enough for the poset situation (see example 1.5, where it is shown that LMD is not a necessary condition for a poset to have a representation). Note that the question of whether LMD is a sufficient condition for representability with respect to all meets and binary joins is raised as open in [5], and appears not to have been resolved.…”
Section: Introductionmentioning
confidence: 99%
“…A partially ordered set (poset) is representable if it can be embedded into a powerset algebra via a map that preserves existing finite meets and joins. The class of representable posets and its infinitary variations have been studied, not always using this terminology, in [8, 1115, 21, 29, 39], generalising work done in the setting of semilattices [2, 9, 27, 33], and for distributive lattices and Boolean algebras [1, 3, 4, 6, 7, 16, 31, 35, 36]. At first glance, it is far from obvious that the class of representable posets is elementary.…”
Section: Introductionmentioning
confidence: 99%
“…A partially ordered set (poset) is representable if it can be embedded into a powerset algebra via a map that preserves existing finite meets and joins. The class of representable posets (RP) and its infinitary variations have been studied, not always using this terminology, in [8,28,20,38,11,13,12,14,15], generalizing work done in the setting of semilattices [2,32,9,26], and for distributive lattices and Boolean algebras [3,35,30,34,4,6,7,1,16]. At first glance, it is far from obvious that RP is an elementary class.…”
Section: Introductionmentioning
confidence: 99%